139 Does Feeding an Increased Level of Narasin (Skycis) Result in Improved Growth Performance and Mortality in a Commercial Wean-to-finish Swine Feeding Program? - Kellner, Trey A (J Anim Sci, 2021)
The response to narasin (Skycis 100, Elanco, Greenfield, IN) to date has been documented in research facilities with a high degree of control and via pigs with no insults to health or feed intake. Furthermore, these studies are always conducted on a single subset of pigs and diets. However, in commercial conditions, the response to narasin must be consistent and defined over a wide range of health statuses, stocking densities, feed intakes, environments, and diet formulations. The objective of this experiment was to determine which inclusion level of narasin (13.6 or 18.1 g/ton) would provide the greatest response under commercial conditions. A total of 197,629 weaned barrows and gilts (6.0 ± 0.1 kg; PIC 337 sired, Hendersonville, TN) were placed in 73 2,400-head commercial wean-to-finish barns that were alternated to 1 of 2 treatments (13.6 or 18.1 g of narasin/ton) in a rolling allotment over an 18-month period. Pigs were on the experiment for an average of 163 ± 1.6 days (until harvest). Throughout the 18-month experimental period, diets (outside of the narasin inclusion) were allowed to change to maximize return over feed costs. Data were analyzed using Proc MIXED (SAS 9.4; Cary, NC) with treatment as the main effect and barn as the experimental unit. Compared to 13.6 g/ton, the increased level of narasin (18.1 g/ton) improved ADG (13.6 g/ton = 0.76 versus 18.1 g/ton = 0.78 kg/d; P = 0.035), gain:feed (13.6 g/ton = 0.389 versus 18.1 g/ton = 0.401; P = 0.042), and mortality from wean to harvest (13.6 g/ton = 7.2% versus 18.1 g/ton = 5.3%; P = 0.084). In summary, feeding an increased level of narasin (18.1 g/ton) during an ever-changing (diet formulation, environment, and health status) commercial experimental conditions resulted in greater growth performance and reduced mortality.